P84/zcc hollow fiber mixed matrix membrane with pdms coating to enhance air separation performance - Norazlianie, Sazali; Nurul, Widiastuti; Triyanda, Gunawan; Hamzah, Fansuri; Wan Norharyati, Wan Salleh; Ahmad Fauzi, Ismail (MDPI, 2020)
This research introduces zeolite carbon composite (ZCC) as a new filler on polymeric membranes based on the BTDA-TDI/MDI (P84) co-polyimide for the air separation process. The separation performance was further improved by a polydimethylsiloxane (PDMS) coating to cover up the surface defect. The incorporation of 1 wt% ZCC into P84 co-polyimide matrix enhanced the O2 permeability from 7.12 to 18.90 Barrer (2.65 times) and the O2/N2 selectivity from 4.11 to 4.92 Barrer (19.71% improvement). The PDMS coating on the membrane further improved the O2/N2 selectivity by up to 60%. The results showed that the incorporation of ZCC and PDMS coating onto the P84 co-polyimide membrane was able to increase the overall air separation performance.